Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1097/01.ju.0000148260.69779.c5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of High Grade Prostatic Intraepithelial Neoplasia and Atypical Small Acinar Proliferation in the Contemporary Era

Abstract: HGPIN found in the contemporary extended biopsy does not warrant repeat biopsy. ASAP continues to be associated with a high risk of cancer and requires at least 1 repeat biopsy using the extended biopsy scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
19

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 19 publications
7
68
1
19
Order By: Relevance
“…Because of the high cancer detection rates, a repeat biopsy should be performed in cases where ASAP is detected. It has been reported that in ASAP cases where the cancer detection rate is high following a repeat biopsy, the regions where ASAP occurred in the initial biopsy should be overemphasized (7,8). According to another study, cancer was detected in 84.8% of cases where a repeat biopsy was performed on the former biopsy area, and in 47.8% of cases where ipsilateral adjacent and contralateral biopsies were performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the high cancer detection rates, a repeat biopsy should be performed in cases where ASAP is detected. It has been reported that in ASAP cases where the cancer detection rate is high following a repeat biopsy, the regions where ASAP occurred in the initial biopsy should be overemphasized (7,8). According to another study, cancer was detected in 84.8% of cases where a repeat biopsy was performed on the former biopsy area, and in 47.8% of cases where ipsilateral adjacent and contralateral biopsies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…ASAP without any findings of malignancy was noted in 5.1% of the results of the initial prostate biopsies. ASAP is described as the presence of atypical glands not diagnostic of prostate cancer, and/or the absence of definitive architectural or cytological features of carcinoma (7,9). A repeat biopsy was performed on patients in whom ASAP was identified in the initial biopsy and who accepted a repeat biopsy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] However, some clinical studies showed that patients with HGPIN have a low risk of further cancer diagnosis but not higher than that observed in cases with a benign diagnosis. [10][11][12][13][14] In any case, after the introduction of extended bioptic schemes with 10/12 samples, the rate of cancer diagnosis after HGPIN decreased from the values up to 80% of the sextant biopsy era to the current 20-30%; probably, owing to a wider sampling, the diagnoses at rebiopsy that were previously not detected at the initial biopsy were avoided. 15 Therefore, it is still debated whether it is really necessary to repeat a biopsy for all the patients with HGPIN and EAU guidelines, 16 generically suggest an early rebiopsy only for multifocal HGPIN.…”
Section: Resultsmentioning
confidence: 99%
“…ASAP is the precancerous lesion most related to PCa (Moore et al, 2005;Amin et al, 2007;Lopez, 2007). By definition, ASAP consists of a focus of small acinar structures formed by atypical epithelial cells and is considered a strong risk factor for PCa.…”
Section: Prostate Cancer Precursorsmentioning
confidence: 99%